Psychological Nature of Personality Self-Realization in Various Scientific Schools - S S Kudinov; N P Avdeyev; K V Arkhipochkina (Peoples' Friendship University of Russia (RUDN University), 2012)
The analysis of various scientific approaches to the research of self-realization of the personality in the domestic and foreign science is submitted in the article.